IMPLEMENTASI PERATURAN DAERAH BARITO TIMUR NOMOR 1 TAHUN 2020 TENTANG PENGELOLAAN SAMPAH DI PASAR TEMENGGOENG DJAJA KARTI KECAMATAN DUSUN TIMUR KABUPATEN BARITO TIMUR - Paulina, Siti; Nurlina, Nurlina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The background of this study is the lack of awareness of traders and the public regarding waste management, the inadequate ability of cleaning staff in handling waste management, the lack of trash bins, and the unavailability of segregated trash bins in the market area. The purpose of this study is to determine the implementation of East Barito Regency Regional Regulation Number 1 of 2020 concerning Waste Management at Temenggoeng Djaja Karti Market, Dusun Timur District, and to identify the factors that influence it. This study uses a qualitative approach with qualitative descriptive. Data collection methods are carried out by interviews, observation, and documentation. Data sources are obtained by purposive sampling technique, which involves 14 respondents. The research results indicate that there are still shortcomings in information dissemination, clarity of communication, and consistency. The number of sanitation workers is sufficient, and information and authority are optimal, but the condition of waste management infrastructure remains inadequate. The placement of sanitation workers and the provision of incentives are considered optimal, and SOP are considered quite optimal. The division of tasks, or fragmentation of responsibilities, between parties has also been implemented according to their respective duties. Supporting factors for implementation include salaries for officers and dissemination of information through public appeals. Inhibiting factors include low levels of market cleanliness compliance and budget constraints. To ensure optimal implementation of this regulation, it is recommended that the Environmental Agency and the Tamiang Layang Market Technical Implementation Unit (UPTD) work together to educate traders and the public about the importance of waste management, including recycling, in the market.